Drought and warming alter gross primary production allocation and reduce productivity in a widespread pasture grass. (23rd April 2022) - Chandregowda, Manjunatha H.; Tjoelker, Mark G.; Power, Sally A.; Pendall, Elise
Abstract: Carbon allocation determines plant growth, fitness and reproductive success. However, climate warming and drought impacts on carbon allocation patterns in grasses are not well known, particularly following grazing or clipping. A widespread C3 pasture grass, Festuca arundinacea, was grown at 26 and 30°C in controlled environment chambers and subjected to drought (65% reduction relative to well‐watered controls). Leaf, root and whole‐plant carbon fluxes were measured and linked to growth before and after clipping. Both drought and warming reduced gross primary production and plant biomass. Drought reduced net leaf photosynthesis but increased the leaf respiratory fraction of assimilated carbon. Warming increased root respiration but did not affect either net leaf photosynthesis or leaf respiration. There was no evidence of thermal acclimation. Moreover, root respiratory carbon loss was amplified in the combined drought and warming treatment and, in addition to a negative carbon balance aboveground, explained an enhanced reduction in plant biomass. Plant regrowth following clipping was strongly suppressed by drought, reflecting increased tiller mortality and exacerbated respiratory carbon loss. These findings emphasize the importance of considering carbon allocation patterns in response to grazing or clipping and interactions with climatic factors for sustainable pasture production in a future climate. Summary Statement: Drought and warming differentially affect carbon partitioning above and belowground in a pasture grass, Festuca arundinacea, and reduce biomass and productivity. Combined drought and warming treatments amplify carbon loss. Clipping during climate extremes, particularly drought, reduces regrowth.